The Maturation of Developmental Concepts in Islamic Thought and Its Impact on Guiding Human Action: The Model of Justice from Theological Belief to Moral Education - Fazry, Hamza (Journal of Humanities & Social Sciences, 2025)
This study aims to examine the concept of justice in Islamic thought by analyzing its intersections across theology, jurisprudence, and spiritual practice (Sufism), and exploring how the concept has matured through these dimensions to guide human action within societies. Justice is treated as a faith-based value grounded in theological principles within Islamic creed (ʿilm al-kalām), then translated into behavioral commitment through doctrine, articulated in jurisprudence as a framework for social order, and embodied in both individual and collective conduct through tazkiyah—spiritual purification—within the ethical system of Sufism. Adopting a descriptive-analytical method, the research examines how this multidimensional approach to justice can provide a foundation for advancing social, economic, and political justice. It concludes that justice in Islam is not merely a legal notion but a mature, holistic process whose theological and educational integration contributes to guiding human action, fostering social stability, and achieving sustainable development. Accordingly, the study recommends further research into other developmental concepts in Islamic thought and their relevance to contemporary social realities using both quantitative and analytical tools. It also proposes adopting conceptual maturity as a framework for renewing theological studies and integrating them into development-focused fields, due to their foundational role in shaping educational action and enhancing social consciousness.
Keywords: Justice; Belief; islamic Thought; Development; Education; Concepts